Comparative cleaning behaviour of Pederson's cleaner shrimp (Ancylomenes pedersoni) between geographically close yet ecologically dissimilar coral reef habitats. (3rd November 2020) - Romain, Joseph J.; Exton, Dan A.; Smith, David J.; Rose, Amelia; Vondriska, Clayton; Titus, Benjamin M.
Abstract: Cleaning mutualisms are important interactions on coral reefs. Intraspecific variation in cleaning rate and behaviour occurs geographically and is often attributed to local processes. However, our understanding of fine-scale variation is limited, but would allow us to control for geography and region-specific behavioural patterns. Here, we compare the cleaning activity of Pederson's cleaner shrimp ( Ancylomenes pedersoni ) on two neighbouring, yet ecologically dissimilar, reef systems in Honduras: Banco Capiro, an offshore bank close to significant land runoff with high coral cover but a depleted fish population, and an oligotrophic fringing reef around the island of Utila, with lower coral cover but high fish abundance and diversity. The proportion of realized to potential fish clientele was <60% at both sites, and the composition of clientele was neither reflective of the demographics of the resident assemblages at each site nor similar between sites. Parrotfishes represented 13–15% of total fish abundance at both sites yet accounted for >50% (Banco Capiro) and 10% (Utila) of all cleans. Conversely, the schoolmaster snapper ( Lutjanus apodus ) represented ~1% of total fish abundance at both sites yet accounted for 40% (Utila) and 1% (Banco Capiro) of all cleans. After standardizing our cleaning rate data by clientele abundance, we find that clientele at Banco Capiro engage in over four times as many cleaning encounters per hour with A. pedersoni than at Utila. Our study highlights the variable nature of coral reef cleaning interactions and the need to better understand the ecological and environmental drivers of this biogeographic variation.